Critical Review of Officials Making Land Deeds Who Do Not Comply With The Procedure For Making Authentic Deeds of Land Sale and Purchase Agreements - Junita, Riska; Rosadiana, Eber; Agustini, Denti Dwi Ayu; Noor, Aslan (Journal of Law, Politic and Humanities, 2024)
The responsibilities of the Land Deed Official (PPAT) include administrative and legal responsibilities. Procedures that are not in accordance with the regulations for making authentic deeds of land sale and purchase agreements will have an impact on the strength of the deed of agreement and even on the Land Deed Making Official himself in accordance with Government Regulation Number 24 of 2016 concerning the Position of Land Deed Making Officials and regulations regarding the Code of Ethics for the Association of Deed Making Officials. Land. The implication of errors in the procedure for making the deed is that the PPAT was dishonorably dismissed from his position, and weakened the strength of the authentic deed of sale and purchase to become a private agreement. Factors that influence PPAT in violating the regulations for making authentic deeds, there are actions that PPAT must take in order to save the sale and purchase transaction, There is mutual trust between the parties including PPAT officials, Time factors and strong relationships cause PPAT to make authentic deeds that are not in accordance with procedures and procedures for making deeds in accordance with applicable regulations.